FACTORS INFLUENCE THE DECISION OF RUBBER FARMERS IN TAKING KUR IN LUBUK RAJA DISTRICT OKU REGENCY - Citra Devi Saputri,; Yetty Oktarina,; Fifian, Fifian Permata Sari (International Journal of Social Science, 2023)
Capital is needed to procure production facilities (seeds, fertilizers, pesticides and equipment), plant maintenance costs, storage, marketing and transportation costs. In rubber farming, a lack of capital causes a lack of input, which raises the risk of failure or low productivity. KUR is MSME credit/financing in the form of working capital and investment supported by guarantee facilities for productive businesses whose distribution is through banks but the source of funds comes entirely from government bank funds with a ceiling of up to IDR 25 million per debtor. This farm credit facility is felt to have helped farmers in carrying out agricultural production activities better in order to achieve higher farmer income. This study examines the factors that influence rubber farmers in taking people's business credit (KUR) to help farmers' capital. The research was carried out deliberately in Lubuk Raja OKU District as a rubber center where many farmers took KUR for capital. The research method used is the survey method and the sampling method uses a simple random method using the slovin formula. The number of samples taken were 83 farmers from 482 farmers. Data analysis using logistic regression. The results of the analysis show that the variables of total family income (X1), land area (X2), production costs (X3) and price (X4) have a significant effect on rubber farmers' decisions in borrowing KUR funds at Bank BRI. Meanwhile, the land ownership status variable (X5) has no significant effect on rubber farmers' decisions in borrowing BRI Bank KUR funds in Lubuk Raja District, OKU Regency.